Research and innovation, a binomio for creation (Gestión y Gerencia, 2024)
Research, innovation, and creation are interconnected terms and processes, whose importance goes beyond their etymology. This essay analyzes and reflects on how the interpretation and connection of these concepts impact the generation of ideas and solutions. It highlights the relationship between research and innovation as catalysts for creation, following the idea of Víctor Morles on the importance of thinking independently, as it is argued that based on the conception one has of this interrelationship, its meaning, significance, and application in practice, one contributes to researching and innovating to create goods and services that address exclusively consumer needs, often superfluous, or to meet the real basic needs of society, its population, in pursuit of their socio-human well-being. For the reflective and analytical generation of knowledge, the methodology of the didactics of questioning (Freire, 1992, Gadamer, cited by Zuleta, 2005) is applied, and the contributions of the authors Víctor Morles, Leal Gutiérrez, and the teacher Simón Rodríguez are examined and incorporated in the foundation of their answers. Some proposals are made to shed light on the Research-Innovation Binomial, enabling the creation of useful knowledge for the Venezuelan context, so that they can materialize from a holistic and comprehensive perspective. Finally, some conclusions about the most important aspects analyzed in the essay are pointed out.
Keywords: Creation; Investigation; Innovation; Integral and integrated rationality; Networking